Influence of water-soluble channeling agents on the release of diclofenac sodium from Irvingia malayana wax matrix tablets - Songwut Yotsawimonwat (2018)
Irvingia malayana wax (IW) is majorly composed of esters of medium chain fatty acids. Its melting point is low and closed to the body temperature. This study aimed at investigating the potential of IW as a matrix-forming agent and evaluate the effect of soluble channeling agents on the release of diclofenac sodium (DS) from IW matrix tablets. The preformulation study by infrared spectroscopy and differential scanning calorimetry showed no incompatibility between IW and DS or soluble channeling agents, namely PEG 4000, PEG 6000 and lactose. IW retarded the release of DS from the matrix tablets more efficiently than carnauba wax due to its greater hydrophobicity and its ability to become partial molten wax at 37°C. Factors affecting the release of DS from IW matrix were drug concentrations, and types and concentrations of channeling agents. The release of DS significantly improved when DS concentration reached approximately 33%. The fast dissolving channeling agent, lactose, could enhance the drug release rate more effectively than PEG 4000 and PEG 6000, respectively. The linear relationship between the DS release rate and the concentration of the chosen channeling agent, PEG 6000, was found (r2=0.9866).